Organizational citizenship behavior (OCB) in relation to job status, job insecurity and work values / Azlyn Ahmad Zawawi, Nur Zafifa Kamarunzaman, Zaliha Hussin - Ahmad Zawawi, Azlyn; Kamarunzaman, Nur Zafifa; Hussin, Zaliha (Institute of Research Management & Innovation (IRMI), 2009)
This study aims to investigate the relationship between organizational citizenship behavior (OCB) and other work related factors; job status, job insecurity and work values. Job status refers to the mode of appointment of employees; either on permanent basis or contractually. OCB has been proven to be a discretionary work behavior that can enhance organizational development and increase work cohesiveness. The sample of the study consists of 200 academicians from local universities. OCB is being measured using Organizational Citizenship Behavior Scale by Podsakoff and Mackenzie (1989) while job insecurity and work values are adapted from Feather and Rauter (2004) and Feather and O’ Brien (1986) respectively. Work values are found to have a moderate correlation with OCB while all other variables are not correlated. OCB, job insecurity and work values are found to have no difference between job status; temporary and permanent.